Main Trends Of Word-Formation Processes In English And Uzbekistan - Uktamova, Mokhigul; Akbaraliyeva, Khurshida (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
This article analyzes the formation of new words and word combinations in English and Uzbek and highlights their main trends. Since each language has its own morphological system and structure, the grammatical structure of the two languages ​​​​is significantly different from each other. This article analyzes these differences comparatively and gives them a definition. Word formation is studied in the lexicology and morphology departments of linguistics, which study words, word formation, word formation methods, and all the phenomena involved in the formation of new words. The results of the article are of great importance in conducting comparative studies in linguistics and in understanding the lexical development trends of both languages.